2012
DOI: 10.3126/njms.v1i2.6616
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Case Report Of Hepatocellular Carcinoma Metastasis To The Chest Wall Presenting As Breast Lump

Abstract: Hepatocellular carcinoma (HCC) is the most frequent primary malignant tumor of the liver. Chronic hepatitis B infection is the most common cause of HCC. Bony metastasis of HCC is usually rare, in which the most common sites involved are vertebra, pelvis, rib and skull. Still rarer are metastasis to the chest wall. Metastatic HCC has an aggressive course and poor prognosis. Hereby, we report an unusual case of HCC metastasis which presented initially as swelling of the anterolateral aspect of the chest wall. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…1 Metastases to the chest wall is an unusual occurrence. 5 A study of 342 patients of HCC with extrahepatic metastasis conducted by Uchino et al found only 8.18% patients to have extrahepatic metastasis on initial presentation. 1 The described case presented solely with an isolated chest wall swelling, diagnosed on FNAC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Metastases to the chest wall is an unusual occurrence. 5 A study of 342 patients of HCC with extrahepatic metastasis conducted by Uchino et al found only 8.18% patients to have extrahepatic metastasis on initial presentation. 1 The described case presented solely with an isolated chest wall swelling, diagnosed on FNAC.…”
Section: Discussionmentioning
confidence: 99%
“…Most common sites of metastasis are lungs, regional lymph nodes, bone, adrenal gland, pancreas, kidney and peritoneum while unusual sites are skeletal muscle and skin 1 . Metastases to the chest wall is an unusual occurrence 5 . A study of 342 patients of HCC with extrahepatic metastasis conducted by Uchino et al found only 8.18% patients to have extrahepatic metastasis on initial presentation 1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the metastatic sites were various, cases with metastatic HCC with no primary sites are occasionally reported. [7][8][9][10][11] Spontaneous tumor regression is rare, but with higher incidence of HCC compared to other cancers. 12 Two meta-analyses on spontaneous regression of primary HCC have been reported, however the mechanism of this phenomenon has not yet been identified.…”
Section: Discussionmentioning
confidence: 99%